Developing a Moderation Community of Practice - Von Konsky, Brian; Watkins, Annette; Broadley, Tania (Massey University, 2012)
This paper reports on a study to evaluate technology-based processes for assessment moderation.The aim was to evaluate standard features found in an institutional Learning Management System,and their compatibility with the values and practices of a large teaching team. The process used anonline discussion board forum for tutors, the paring of more experienced tutors with those new tothe process, and further meetings conducted in both face-to-face and web conferencingenvironments. Online rubrics were used for assessing student work and the provision of feedback.A focus group conducted after marking was concluded and the analysis of the discussion boardforum demonstrated a strong community of practice with a shared understanding of assessmentrequirements.